Efficient, Rapid, and Sensitive Detection of Plant RNA Viruses With One-Pot RT-RPA–CRISPR/Cas12a Assay - Aman, Rashid; Mahas, Ahmed; Marsic, Tin; Hassan, Norhan; Mahfouz, Magdy M. (Frontiers in Microbiology, 2020)
Most viruses that infect plants use RNA to carry their genomic information; timely and robust detection methods are crucial for efficient control of these diverse pathogens. The RNA viruses, potexvirus (Potexvirus, family Alphaflexiviridae), potyvirus (Potyvirus, family Potyviridae), and tobamovirus (Tobamovirus, family Virgaviridae) are among the most economically damaging pathogenic plant viruses, as they are highly infectious and distributed worldwide. Their infection of crop plants, alone or together with other viruses, causes severe yield losses. Isothermal nucleic acid amplification methods, such as loop-mediated isothermal amplification (LAMP), recombinase polymerase amplification (RPA), and others have been harnessed for the detection of DNA- and RNA-based viruses. However, they have a high rate of non-specific amplification and other drawbacks. The collateral activities of clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated nuclease Cas systems such as Cas12 and Cas14 (which act on ssDNA) and Cas13 (which acts on ssRNA) have recently been exploited to develop highly sensitive, specific, and rapid detection platforms. Here, we report the development of a simple, rapid, and efficient RT- RPA method, coupled with a CRISPR/Cas12a-based one-step detection assay, to detect plant RNA viruses. This diagnostic method can be performed at a single temperature in less than 30 min and integrated with an inexpensive commercially available fluorescence visualizer to facilitate rapid, in-field diagnosis of plant RNA viruses. Our developed assay provides an efficient and robust detection platform to accelerate plant pathogen detection and fast-track containment strategies.